Echocardiographic Assessment of Pulmonary Arterial Hypertension for Pediatricians and Neonatologists - Skinner, Gregory James (Frontiers in Pediatrics, 2017)
There is a growing awareness of the role that increased pulmonary vascular resistance (PVR) plays in many pathologies, therefore assessment of pulmonary artery pressure is an increasingly requested investigation in the critical care environment. This article will go through the basic concepts regarding pulmonary artery pressure (PAP) and PVR, then will go on to outline the various echocardiographic parameters which are used to assess them. Finally, an outline of how to undertake this assessment will be presented.